Epithelioid hemangioendothelioma of spine: A case report with review of literatures - Ping-Kang Chen, MS (Radiology Case Reports, 2020)
Primary epithelioid hemangioendothelioma of the spine is the extremely rare malignant vascular neoplasm with an unpredictable outcome. A case of epithelioid hemangioendothelioma with multiple lytic lesions of thoracolumbar spine and other bones in a 29-year-old male patient is reported. A review of the published data regarding this rare neoplasm is also presented. The features of epithelioid hemangioendothelioma include the occurrence in the young male patient, multiple osteolytic lesions with thin sclerotic rim and hypermetabolic activities. However, its imaging features are not specific. Positron emission tomography/computed tomography is essential for identification of the lesions and subsequent follow-up for treatment.